(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2016)
In Moral Tribes, Greene (2013) promotes the proposition that emotions are crucial for everyday decision making. The author thereby introduces subjectivity into the contemporary philosophical landscape, which is dominated by an analytic orientation and a need for objectivity. This perspective has philosophical and practical implications.